Base Deficit and Increased Lactate Level as Predictors of Blood Transfusion in Trauma Patients With Acute Bleeding at the Emergency Department RSUP Prof. dr. I.G.N.G. Ngoerah - Nenoharan, Esther Gisela; Widnyana, I Made Gede; Hartawan, IGAG Utara; Wiryana, Made; Senapathi, Tjokorda Gde Agung; Sucandra, I Made Agus Kresna; Dewi, Dewa Ayu Mas Shintya; Pradana, FX Adinda Putra; Wigundwipayana, Kadek Anggie (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Bleeding caused by trauma is still a prominent factor in death and organ system complications. Base deficit (BD) and lactate levels are experiencing disturbances which result in hypoxic acidosis conditions at the tissue and cellular levels.Objective: This study aims to determine the relationship between low base deficit levels, high lactate values, related to the need for blood transfusions in trauma patients with acute blood loss.Method: This research is an observational analytic study with a prospective cohort study design. The target population of this study were all trauma patients with acute bleeding admitted to the emergency room Prof Dr. dr. IGNG Ngoerah.Result: Age results showed a mean ± SD of 25.08 ± 6.38 years, the most gender was male, there were 36 subjects (72%), Hb levels had an average of ± 10.47 ± 2.85 g/dL, BMI results had mean ± SD 23.47 ± 3.54 kg/m2, the most common type of trauma was multiple trauma, the ISS score was found to have a mean ± SD 23.38 ± 9.09. The results for the value of the base level obtained a mean ± SD of 4.08 ± 5.08 mmol/L, with the transfusion group with an average of -6.41 ± 4.65 mmol/L. Low base level <-3 mmol/L had RR 3.69 (95% CI 1.83-7.45; P<0.001) and Adj RR 18.56 (95% CI 14.00-24.75; p=0.002 ). The average lactate result was found to have a mean ± SD 3.77 ± 2.29 and in the transfusion group 4.78 ± 2.38 mmol/L with high lactate levels (> 4 mmol/L) RR 5.53 (CI 95% 2, 25-13.64; P<0.001) and Adj RR 41.21 (95% CI 35.05-57.74; p<0.001).Conclusion: Low base deficit and high lactate levels are associated with the need for blood transfusions in patients with acute bleeding.